Rekwizyt – atrybut – gadżet. O społecznych funkcjach znaków addytywnych - Hendrykowski, Marek (Przestrzenie Teorii, 2023)
The article presents a panorama of selected topics and research issues relating to the functional characteristics of props, both in the past and present.